Filosofia da educação : grandes problemas da pedagogia moderna, de Theobaldo Miranda Santos: um estudo sobre manuais de ensino - Silva, Rafael Fernando da [UNESP] (2014)
This masters dissertation presents the results of studies and researches on the teaching manual titled Philosophy of Education: major problems of the modern pedagogy (Filosofia da educação: grandes problemas da pedagogia moderna, in Portuguese), by Theobaldo Miranda Santos. These studies were oriented by Professor Carlos Monarcha. The dissertation aims at contributing to the knowledge production on Education, through the study and analysis of a teaching manual produced by a representative (in the intellectual and educational fields), Catholic author. For that, we prioritized the study of works in the genre “teaching manuals”, published alone or in collections aimed at the training of primary and secondary teachers